PENERAPAN PSAK No. 109 TENTANG AKUNTANSI ZAKAT DAN INFAK/ SEDEKAH PADA BADAN AMIL ZAKAT NASIONAL KABUPATEN PURWAKARTA - Khania Putri Utami; Wirman . (Jurnal Mirai Management, 2021)
Islamic accounting has become an alternative that can be used as a substitute for conventional accounting, which is generally used by Islamic institutions, such as BAZNAS. The purpose of this study was to determine whether BAZNAS Purwakarta Regency has implemented the provisions contained in PSAK No. 109 regarding Accounting for Zakat, Infaq/Alms well. The research methodology used in this research is descriptive – qualitative method. The data in this research are secondary where the data is obtained through journals or scientific articles and books related to this research. The results of the study indicate that in general, the National Amil Zakat Agency of Purwakarta Regency has properly implemented PSAK No. 109 concerning Accounting for Zakat, Infaq/Alms, both in recognition, measurement, presentation and disclosure.